Predicción de la disposición a consumir alimentos de marcas saludables mediante la teoría del comportamiento planificado: El papel de la alfabetización nutricional - Chilón Troncos, Ronny Francisco (2023)
Maintaining good eating practices is a factor that allows a healthy life; therefore, it is necessary to promote health, being a fundamental tool, nutritional literacy. In this context, this study aims to validate the psychometric characteristics of the S-NutLit scale to assess nutritional literacy. It is a variable made up of two dimensions, and data were collected from a sample of 396 Peruvian adults. By means of an instrumental study, indicators of acceptable reliability were obtained, having also an ideal measurement model to evaluate nutritional literacy in the Peruvian context, which is composed of 11 items. Thus, the aim is to reinforce health promotion activities through a nutritional literacy diagnosis, which due to its characteristics, can be self-administered and used by health entities and other entities in general that are interested in knowing the feeding practices of an individual, which undoubtedly lead to good health.